2010
DOI: 10.4314/acsj.v17i3.54213
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of the correlation between molecular and morphological traits in assorted maize inbred lines

Abstract: The success in identifying heterosis in hybrid maize (Zea mays L.) breeding depends on the availability of reliable genetic diversity among maize inbred lines. Conventional methods of breeding have been boosted by the availability and efficiency of molecular markers. Coupling simple sequence repeat (SSR) markers with morphological markers provides thorough starting information for new inbred lines, especially from different genetic backgrounds. Furthermore, recent evidences that the environment can influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…In agreement to this finding, Dagne (2008) reported a low correlation coefficient (r= 0.09) between morphological and SSR-based genetic distance measures among 35 QPM inbred lines using 40 SSR markers. Karanja et al (2009) found a correlation coefficient of 0.2323 with p value of 0.012 between SSR and morphological data in assorted maize inbred lines. Amelework et al (2016) also reported that there was no significant relationship between molecular and morphological distances in a study conducted using 30 SSRs and 36 sorghum genotypes.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In agreement to this finding, Dagne (2008) reported a low correlation coefficient (r= 0.09) between morphological and SSR-based genetic distance measures among 35 QPM inbred lines using 40 SSR markers. Karanja et al (2009) found a correlation coefficient of 0.2323 with p value of 0.012 between SSR and morphological data in assorted maize inbred lines. Amelework et al (2016) also reported that there was no significant relationship between molecular and morphological distances in a study conducted using 30 SSRs and 36 sorghum genotypes.…”
Section: Discussionmentioning
confidence: 86%
“…Morphological and molecular markers and pedigree analyses are widely used in germplasm characterization and to establish genetic diversity and relationship in crop plants (Warburton et al, 2005). Morphoagronomic traits are among the earliest markers widely used in germplasm characterization, management and utilization (Smith and Smith, 1992;Karanja et al, 2009;Sow et al, 2014). Abu-Alrub et al (2006) used kernel characteristics as the best descriptors followed by ear traits for classifying Peruvian highland maize germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…These results are also supported by Shahrokhi and Khavarikhorasani (2013), who reported on the effectiveness of phenotypic traits as they grouped 28 maize hybrids into four clusters. Furthermore, Karanja et al (2009) reported that both phenotypic traits and SSR markers were effective in clustering inbred lines. Pedigree analysis placed 119 inbred maize lines into eight and SSR markers resulted in clustering the inbred lines into 10 groups (Reid et al, 2011).…”
Section: Genetic Distancementioning
confidence: 99%
“…In this study, mean of alleles per locus was considerably lower than reported earlier in the maize. Karanja et al, (2009) reported 2.0 averages of alleles using 14 loci. The SSRs used in this study were tri-repeat motifs (thirty nine loci), di and tetra-repeat (one locus each) whereas; information of one repeat motif was not available at MaizeGDB.…”
Section: Resultsmentioning
confidence: 99%